Sistem Pendukung Keputusan Pemilihan Koordinator Konsiyansi Menerapan Metode ARAS - Tiurima Tampubolon; Mesran (Journal of Informatics Management and Information Technology, 2022)
Coordinator is a person who has experience, knowledge and good skills to lead and process and develop a product or an organization to achieve a goal. Consignment is a form of sales cooperation carried out by the owner of goods/products with distributors (stores/distros/ company). Consignment Coordinator is a person who is given the responsibility to control, process and develop goods that have been entrusted by the product owner to the store so that the product that has been deposited can generate profits for the product owner. The problem faced in choosing a consignment coordinator is that the recruitment process is still done manually. Another problem is that the recruited consignment coordinator does not have the ability and quality as desired by the company. .Decision Support System is an information system that produces alternative decisions to solve a problem. The Decision Support System to determine the consignment coordinator can be generated based on several criteria in determining a criterion that is made to prevent mistakes made by certain parties. Many methods are used in the Decision Support System, including the AHP, TOPSIS, SAW, VIKOR, MOORA, ARAS and many other methods. The ARAS method is the right method for determining qualified consignment coordinator candidates. The ARAS (Additive Ratio Assessment) method is a comprehensive frame of mind method considering the hierarchical process which is then calculated by weight to calculate a criterion in determining the acceptance of the coordinator consignment